Enhanced Near‐Infrared Shielding and Light Scattering Using Surface‐Roughened Hybrid Hollow Microparticles Synthesized with Polymer and TiO2@Al(OH)3 for Cosmetic Applications. (7th May 2018) - Han, Nuri; Kim, Min Gyu; Kim, Sung Wook; Shin, Min Kyu; Kim, Su Ji; Kim, Moo Sung; Lee, Sang Rin; Lee, Jun Bae; Pyun, Seung Beom; La, Ju A; Song, Ji Eun; Cho, Eun Chul
Abstract: Some materials and their micro‐/nanostructures are explored to shield near‐infrared (NIR) light. However, the structural role of polymeric matrices in terms of the sensitivity to NIR light and the scattering/absorption characteristics of particles bearing inorganic colloids lack understanding. To understand this issue further, a polymer–inorganic hybrid microparticle is synthesized, where submicrometer‐sized TiO2 core‐thin aluminium hydroxide shell colloids (TiO2 @Al(OH)3 ) are dispersed in a roughened polymer hollow particle matrix. They exhibit higher light extinction at NIR frequencies and higher light scattering efficiencies in the NIR regions compared to hybrid solid microparticles and a simple mixture of inorganic and polymer hollow microparticles. Owing to these characteristics, a cosmetic formulation containing the roughened hybrid hollow microparticles effectively suppresses the increase in the temperatures of artificial skin upon the illumination of a simulated sunlight, without displaying skin whitening which is caused by including much inorganic colloids in the formulation. The present results are helpful to those who manipulate the optical characteristics of inorganic particles whose geometries are hardly tailored. The results are also practically helpful to those who want to block NIR light by reducing the amount of inorganic particles. Abstract : A surface‐roughened polymer–inorganic hollow hybrid particle bearing submicrometer‐sized TiO2 @Al(OH)3 colloids in a polymer hollow matrix is synthesized for enhanced near‐infrared shielding and light scattering. A cosmetic formulation containing the hybrid hollow microparticles effectively suppresses the increase in artificial skin temperatures upon exposure to a simulated sunlight.